KNOWLEDGE OF DENTAL STUDENTS ON THE MANAGEMENT OF FURCATION PERFORATION IN PERMANENT MOLARS - CAMPOS, Fernanda De Araújo Trigueiro; SOUSA, Consuelo Fernanda Macedo De; RIBEIRO, Isabella Lima Arrais; SILVA, Silmara de Andrade (Revista Brasileira de Ciências da Saúde, 2016)
Introduction: Dental perforations – communication between support structures and root canals - are likely to happen during endodontic treatment. The appropriate management of a perforation is essential for the good prognosis of the tooth. Objective: To evaluate the knowledge of dental students on how to manage cases of furcation perforation in permanent molars. Material andMethods:This was a quantitative, exploratory and descriptive research study. The data collection instrument was a questionnaire with ten questions answered by 179 dental students from the 5th to the 10thcourse semester. Results: The results showed that 42.46% of the participants would perform cleaning and application of MTA.The majority of them(38.55%)reported thatthe presence of infected tissue apically to the perforation is the most influential factor in the prognosis. As for the immediate clinical signs, most respondents(44.69%) reported that the patient complains of sensitivity to the endodontic file, persistent bleeding and edema, although edema is not an immediate event. The most selected treatment sequence(40.88%) was to perform thorough irrigation of the area with 2.5% sodium hypochlorite, wait for hemostasis, and then apply the sealing material. Thus, respondents failed to report the use of 1% sodium hypochlorite. A total of 45.81% of the respondents reported that prevent bone resorption and loss of periodontal ligament are the main purpose of performing perforation sealing. Conclusion: We conclude that the surveyed dental students would poorly managea case of furcation perforation, particularly as regards the recognition of the clinical signs and treatment sequence.DESCRIPTORS: Root Canal Preparation. Tooth Root. Molar